2020
DOI: 10.1002/jum.15470
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Large‐for‐Gestational‐Age Neonates by Different Growth Standards

Abstract: Objective Compare the accuracy of the Hadlock, the NICHD, and the Fetal Medicine Foundation (FMF) charts to detect large‐for‐gestational‐age (LGA) and adverse neonatal outcomes (as a secondary outcome). Methods This is a secondary analysis from a prospective study that included singleton non‐anomalous gestations with growth ultrasound at 26–36 weeks. LGA was suspected with estimated fetal weight > 90th percentile by the NICHD, FMF, and Hadlock charts. LGA was diagnosed with birth weight > 90th percentile. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Analysis of per country performance is summarized in eTable 4 in Supplement 1, which shows that the accuracy of Hadlock-based GA estimates are close to Hadlock in the US (mean [SD], NICHD MAE, 4.79 [4.16] days; Hadlock MAE, 4.90 [4.32] days), while outperforming Hadlock significantly in the Zambia population (mean [SD], NICHD MAE, 4.96 [4.84] days; Hadlock MAE, 5.62 [5.20] days). The Intergrowth-21st formula performed significantly worse than Hadlock and NICHD across both populations as demonstrated in other studies . Our ensemble model estimate was compared against NICHD, and the result showed that the ensemble model had a lower MAE for both US (mean [SD] difference 3.58 [2.79] days; 95% CI, −1.90 to −0.70 days) and Zambia (mean [SD] difference, 3.70 [3.57] days; 95% CI, −1.80 to −0.60 days), demonstrating robustness and statistical superiority on all subgroups.…”
Section: Resultssupporting
confidence: 70%
“…Analysis of per country performance is summarized in eTable 4 in Supplement 1, which shows that the accuracy of Hadlock-based GA estimates are close to Hadlock in the US (mean [SD], NICHD MAE, 4.79 [4.16] days; Hadlock MAE, 4.90 [4.32] days), while outperforming Hadlock significantly in the Zambia population (mean [SD], NICHD MAE, 4.96 [4.84] days; Hadlock MAE, 5.62 [5.20] days). The Intergrowth-21st formula performed significantly worse than Hadlock and NICHD across both populations as demonstrated in other studies . Our ensemble model estimate was compared against NICHD, and the result showed that the ensemble model had a lower MAE for both US (mean [SD] difference 3.58 [2.79] days; 95% CI, −1.90 to −0.70 days) and Zambia (mean [SD] difference, 3.70 [3.57] days; 95% CI, −1.80 to −0.60 days), demonstrating robustness and statistical superiority on all subgroups.…”
Section: Resultssupporting
confidence: 70%
“…Use of the normogram of Alexander et al 18 to identify SGA neonates may also be considered a limitation, as it uses actual birth weight and tends to underestimate the true prevalence of neonates with suboptimal growth. However, the same charts have been utilized to assess neonatal-weight disorders in prior studies 29,30 . Finally, we did not report monitoring methods such as Doppler, cardiotocography and biophysical profiles for growth-restricted fetuses and how these tests may have impacted on the timing and outcome of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In their low‐risk pregnant population, Duncan et al . 18 found that the FMF growth chart had the highest accuracy for detection of LGA (AUC, 0.8). Similarly, in an obese population without diabetes, Verger et al .…”
Section: Discussionmentioning
confidence: 95%
“…The NICHD growth chart was selected because of its focus on including a racially and ethnically diverse contemporary population 11 , and because prior research has suggested it has a higher screen‐positive rate for EFW ≥ 90 th percentile compared with other growth charts 17 . The FMF growth chart was selected because it may improve the ability to predict LGA compared with the Hadlock growth chart in low‐risk individuals without pregestational diabetes 18 . At the time at which the current study was conducted, our institution utilized the Brenner growth chart, and has more recently transitioned to the Hadlock growth chart.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation